Pengembangan Indeks Wakaf: Studi Kasus Kabupaten/Kota di Provinsi Banten - Arief Fitrijanto; Bambang Juanda; Sri Mulatsih; Muhammad Findi (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
The implementation of regional autonomy in Indonesia is still hampered by low fiscal independence, which hinders the provision of public goods such as educational infrastructure. This study aims to develop and test the Regional Waqf Index (IWW) as an instrument to measure waqf potential at the district/city level to map alternative social financing sources. Referring to the OECD framework (2008), IWW is constructed through three dimensions: Awareness, Quantity, and Capacity. The study was conducted in eight districts/cities in Banten Province using a combination of primary data (literacy surveys) and secondary data (macroeconomic indicators). Data analysis used the Min-Max normalization method and geometric mean aggregation. The results show that the majority of areas in Banten (62.5%) are in the "Sufficient" category. There is significant heterogeneity; urban areas and industrial centers have a higher index than the southern region which is constrained by the economic capacity dimension. This finding confirms the strategic role of waqf as a fiscal supplement for urgent public needs, such as the renovation of educational facilities. Research recommendations emphasize strengthening waqf literacy in high-economic-capacity regions and increasing the professionalism of Nazhir to optimize the realization of waqf collection in the regions.